Ultrasonographic Evaluation of Fetal Brain Midline Structures in The Second Trimester: The role of 2D versus 4D, with Post-Natal Correlation - Ahmed Bedeir Abd El Salam (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Midline cerebral structures are essential for the normal morphogenesis and function of the fetal brain. However, the diagnosis of congenital anomalies of midline cerebral structures. The Aim of The Work: This study aimed to evaluate the role of 2D versus 4D ultrasound in the diagnosis of midline structures of the fetal brain at the second trimester of pregnancy.Patients and Methods: 200 pregnant women at the second trimester [18-22 weeks] were selected. They were clinically evaluated to check the female and fetal wellbeing. Then a screening of fetal brain midline strictures had been performed by two- and four-dimensional ultrasound, aiming to discover any anomalies of the fetal brain midline structure. Both scans were compared with the postnatal transcranial ultrasound.Results: The 2D ultrasound detected no abnormality in 194 out of 200 fetuses [97.0%], and 4 cases [2.0%] had mega-cisterna magna, and 2 cases [1.0%] had encephalomylocele, which were detected by the 4 D and confirmed by postnatal transcranial ultrasound. The 4 D US discovered 2 cases [1.0%] of Dandywalker malformation, which was confirmed by postnatal transcranial US. There was a complete agreement between prenatal 4D ultrasound and postnatal transcranial ultrasound. The prenatal 2D ultrasound had a sensitivity of 75.0%, specificity of 100.0%, PPV of 100.0%, NPV of 98.7% and overall accuracy of 99.0%. Otherwise, the prenatal 4D ultrasound was 100.0% sensitive and specific.  Conclusion: 4D ultrasound showed superiority in the diagnosis and confirmation of the fetal brain midline structure’s abnormalities. Also, the prenatal 4D ultrasound was 100.0% sensitive as postnatal transcranial US.